Examining migration policies in countries of origin and destination countries - Leow, Joy (2017)
Large scale migration as an impact of globalization and technological developments are a hallmark of the 21st century. This paper aims to identify why people migrate, and its impact from the policies in their countries of origin and destination. The paper examines primarily the push and pull factors surrounding economic migrants moving from developing to more developed states. Also, in doing so, examining the relationships that determine choice of destination country. In order to illustrate this specific flow of migration, the paper will look at case studies of Singapore, as a destination country, and Philippines, as a country of origin.